Penyuluhan Kesehatan Reproduksi dan Senam Dismenore: Strategi Partisipatif Meningkatkan Pengetahuan dan Kesehatan Remaja Putri - Masrina Munawarah Tampubolon; Nabilah Siregar; Widia Lestari; Chesy Chesy; Dafri Dafri; Dini Dini; Putri Putri; Siti Siti; Fandra Fandra; Fitri Fitri; Hasniati Hasniati; Irza Irza; Monika Monika; Nathania Nathania; Septia Septia; Septiana Septiana (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescent girls are a vulnerable group to reproductive health issues, particularly a lack of knowledge about menstrual care and dysmenorrhea, which can disrupt daily activities. This community service activity aims to improve adolescent girls' knowledge and skills in maintaining reproductive health and implementing non-pharmacological methods to reduce menstrual pain. The program involved 30 participants through participatory health education and demonstrations of dysmenorrhea exercises at MTs Bustanul Ulum, Pekanbaru City. Evaluation was conducted using pre- and post-tests. Results showed a significant increase in knowledge scores from 83.33 to 98.33, as well as improved ability to perform the exercises correctly. Most participants also reported reduced pain and greater relaxation. This activity effectively increased reproductive health literacy and introduced safe alternatives for managing menstrual pain.